Isolated folate deficiency causing profound pancytopenia in pregnancy - Obaji, Samya Gwen (BMJ Case Rep, 2015)
New-onset pancytopenia in pregnancy is challenging in the clinical setting particularly as the management and outcome of pregnancy are entirely dependent on the underlying aetiology. In the absence of increased peripheral destruction, for example, hypersplenism, bone marrow (BM) failure should be considered as the cause of pancytopenia. Profound folate or B(12) deficiency may result in BM failure and are relatively easy to diagnose and manage. Other causes include aplastic anaemia (AA), infiltration by a haematological malignancy and other non-haematological disorders. We report a 26-year-old woman presenting with severe pancytopenia due to folate deficiency with complete recovery observed after folic acid replacement. This case highlights the importance of recognising folate deficiency as a reversible cause of pancytopenia, since prompt replacement can lead to rapid normalisation of counts with no subsequent clinical sequelae. We also consider the indications for measuring serum folate in pregnancy.